If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2m + 2 = 10 Reorder the terms: 2 + -2m = 10 Solving 2 + -2m = 10 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -2m = 10 + -2 Combine like terms: 2 + -2 = 0 0 + -2m = 10 + -2 -2m = 10 + -2 Combine like terms: 10 + -2 = 8 -2m = 8 Divide each side by '-2'. m = -4 Simplifying m = -4
| X^2=x^2+169 | | 3(2-x)-6=6 | | 7x-18+3x+10=32 | | W+8=24 | | 3x+2y=3600 | | (3x-2y)(5x+y)= | | x^2+4xy=19 | | 2x=2x+14 | | (5-x/2)=-4 | | 3(m+5)-6=3(m-3) | | (5-x/2)=-14 | | 3x+2y=4800 | | 5-x/2=-4 | | F=(28+3S)KN | | 5y-8+y=1 | | 2x+6=4x+9 | | 5y-8-y=1 | | 2x+6=4+9 | | 5x=x+t | | 9X+5Y=-56 | | X+xy+y=21 | | 3x+8=-4+71 | | 7=-3-4b | | 5u+5(1-6)=u+8 | | 5x-3=6x+2x-9 | | 2cos^2(x)-sin(x)=0 | | 4*ln(x)-x=6 | | -3+6=2x-9 | | X^5/3=0.5 | | 10x-7(3)=-18 | | 17a-4= | | 4(3x-8)=28 |